Role of targeted policies in mainstreaming renewable energy in a resource constrained electricity system: A case study of Karnataka electricity system in India. (July 2017) - Amrutha, A.A.; Balachandra, P.; Mathirajan, M.
Abstract: India is aggressively pursuing its renewable energy capacity expansion goals. Targeted policies such as Feed-in Tariff (FIT), Renewable Purchase Obligation (RPO) and Renewable Energy Certificate (REC) are introduced to stimulate renewable energy capacity expansion as well as generation. Currently, Indian power utilities treat RPO targets as a cost-burden, and therefore there is prevalence of non-compliance. Even other policies, such as FIT and RECs, in their present form, have failed to influence increase in renewable electricity supply. This has lead us to raise an important question whether these policies are adequate for building a cost-effective renewable energy-based low carbon electricity system for India. In this paper, we discuss the impact of above targeted policies in increasing the share of renewable electricity generation in the case of Karnataka State Electricity System. Various scenarios are developed and analysed using mixed-integer programming model to study the impacts. The results suggest that optimally managed FIT and REC schemes can provide opportunities for utilities to benefit from reduced costs. Overall, the above policies are inadequate, and introduction of market-based incentives, which expand the scope of trading in renewable energy certificates, are essential to achieve the desired objectives. Highlights: Analysing impacts of targeted energy policies in increasing renewable electricity share. Scenario analyses are used to study impact on costs, targets, shortages and compliance. Current policies are inadequate to ensure renewable energy utilization beyond targets. Policies are necessary to incentivise compliance and penalise non-compliance.